IgG4-related diseases involving pleura: a case report and literature review - Zuo, Anli; Liu, Xinyi; Guo, Zihan; Jiang, Yunxiu; Lu, Degan (Frontiers in Medicine, 2023)
Immunoglobulin G4-related disease (IgG4-RD) is a systemic fibro-inflammatory disease with the potential to involve virtually all organs, including the pancreas, kidneys, lungs, and pleura, amongst others. IgG4-RD pleural involvement may cause diverse complications such as pleural effusion, pleural thickening, pleural nodules, and additional lesions, which can be presented in many clinical diseases. However, isolated cases of pleurisy are still rare in IgG4-RD. We report a 72-year-old patient who was admitted to our hospital with cough, expectoration, and fatigue. He had a right-sided pleural effusion, and the tissue evaluation of the pleural biopsy by medical thoracoscopy met the diagnostic criteria of IgG4-RD. His serum IgG4 levels were elevated and he was finally diagnosed with IgG4-RD pleural involvement. He was subsequently started on prednisone 40 mg daily and his pleural effusion was almost disappeared 2 weeks later. This paper reported a case of IgG4-RD who had exclusive involvement of the pleura and highlighted the significance of considering IgG4-RD as a potential diagnosis in patients with unexplained pleural effusion.